Composite metal oxide for preparing aromatic hydrocarbon from synthesis gas and application of composite metal oxide

By using a dual-function catalyst composed of indium doped high entropy nanocomposite metal oxide and silicon-aluminum molecular sieve, the problem of high CO2 selectivity during the conversion of aromatic hydrocarbons in the synthesis gas is solved, and efficient and stable aromatic hydrocarbon preparation is achieved.

CN119819355AActive Publication Date: 2025-04-15SHANGHAI ADVANCED RES INST CHINESE ACADEMY OF SCI
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510041781.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-15
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

In the prior art, during the conversion of synthesis gas into aromatic hydrocarbons, CO2 is highly selective and the reaction efficiency has not been fully improved.

Method used

Indium-doped high-entropy nanocomposite metal oxides are used as catalysts to decompose metal precursors at high temperatures through high boiling point organic solvents to prepare indium-doped high-entropy nanooxides, and combine silicon-aluminum molecular sieve to form a bifunctional catalyst.

Benefits of technology

The selectivity of CO2 in the product is significantly reduced, the selectivity of aromatic hydrocarbons is improved, and the stability and reaction efficiency of the catalyst are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237175090000081
    Figure BDA0005237175090000081
  • Figure BDA0005237175090000091
    Figure BDA0005237175090000091
  • Figure HDA0005237175100000011
    Figure HDA0005237175100000011
Patent Text Reader

Abstract

The invention provides a composite metal oxide for preparing aromatic hydrocarbon from synthesis gas and application of the composite metal oxide. Raw materials of the composite metal oxide comprise chromium salt, indium salt, ferric salt, zinc salt and aluminum salt. The indium oxide of the composite metal oxide has relatively high CO hydrogenation and reverse water gas change reaction activity, not only can improve the activity of converting CO on the oxide into an oxygen-containing intermediate, but also can optimize the product distribution and effectively reduce the CO2 selectivity in the product, and also has relatively high aromatic hydrocarbon selectivity; the catalyst can catalyze synthesis gas to be converted into aromatic hydrocarbon, the selectivity of a by-product CO2 is low, the reaction efficiency is high, and oxides are not prone to inactivation. Besides, the composite metal oxide prepared by decomposing the metal precursor at a high temperature by using the high-boiling-point organic solvent has a relatively stable structure, so that the migration of metal to the molecular sieve is effectively inhibited, and the reaction stability of preparing the aromatic hydrocarbon from the synthesis gas is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aromatic hydrocarbon preparation, and particularly relates to a composite metal oxide used for preparing aromatic hydrocarbons from synthesis gas and application thereof. Background Art

[0002] Aromatics, as a kind of vital basic chemical raw materials, are currently mainly obtained from petroleum resources by naphtha reforming or oil cracking technology. However, with the increasing consumption of oil and the depletion of oil resources, the preparation of aromatics through synthesis gas (CO+H2) from non-petroleum resources (such as coal, natural gas, biomass and CO2) has shown great development potential. In the traditional synthesis gas conversion to hydrocarbon compounds, namely the Fischer-Tropsch synthesis (FTS) reaction, the main products are chain hydrocarbons, and the distribution of these products follows the ASF law, resulting in very low aromatic selectivity. In order to obtain more aromatic products, another feasible strategy is to adopt a two-step method. Specifically, the method first converts the synthesis gas into methanol through a methanol synthesis step, and then uses methanol to aromatics (MTA) to realize the conversion of synthesis gas to aromatics. However, the two-step method has problems such as many processes and high energy consumption, which restricts its further industrialization.

[0003] In recent years, based on the reaction coupling strategy, the highly selective conversion of syngas to aromatics has been successfully achieved by connecting oxides and MTA molecular sieves in series for syngas to methanol. However, the methanol-mediated route still has problems such as low CO conversion rate and high selectivity of byproduct CO2, and its reaction efficiency needs to be further improved. Patent CN202211202019.5 discloses a Mn-based metal oxide with at least one of Ce, Zr, Ti, Fe and Ni loaded on the surface, which is used in the syngas to aromatics reaction, significantly improving the CO conversion rate and aromatics yield. CN202211314164.2 discloses a syngas to aromatics catalyst with higher CO conversion rate and aromatics selectivity, the catalyst comprising ZnO, Cr2O3, ZrO2, MnO x , CeO2, Ga2O3, ZnTi, ZnZr, ZnCr, MnCe, MnZr, GaZr. Patent CN114588902A discloses a catalyst for converting synthesis gas to aromatics, its preparation method and application, the catalyst uses Fischer-Tropsch metal-modified metal oxide, wherein the modified metal is at least one of Fe, Co, Ru, Ni, wherein Fe, Co, Ru, Ni loaded on the composite oxide also has the effect of improving the synthesis gas conversion efficiency.

[0004] Patent CN202110456312.3 discloses a method for preparing a synthesis gas to aromatics catalyst composed of a silicon-aluminum molecular sieve and a multiphase metal oxide, wherein the multiphase metal oxide is at least two of cerium oxide-zirconium oxide, zinc oxide-chromium oxide, and zinc oxide-zirconium oxide. Patent CN202211179273.8 discloses a short b-axis HZSM-5 zeolite molecular sieve, and the use of Zr-Zn metal oxide and short b-axis HZSM-5 zeolite molecules for the preparation of aromatics.

[0005] However, the doping of metal elements in the above patent documents can only improve the CO conversion rate in the conversion of synthesis gas to aromatics, and cannot significantly reduce the CO2 selectivity. In summary, the CO2 selectivity of the above catalysts is still relatively high.

[0006] Therefore, it is of great significance to develop a catalyst for converting syngas to aromatics with high reaction efficiency and low CO2 selectivity. Summary of the invention

[0007] In view of the shortcomings of the prior art described above, the object of the present invention is to provide a method for preparing an indium-doped high-entropy nanocomposite metal oxide and applying it to synthesizing aromatics from syngas, so as to solve the problems in the prior art. To achieve the above object and other related objects, the present invention is obtained through the following technical solutions.

[0008] The invention provides a composite metal oxide, wherein the raw materials of the composite metal oxide include chromium salt, indium salt, iron salt, zinc salt and aluminum salt.

[0009] In certain embodiments, the molar ratio of the chromium element, indium element, iron element, zinc element and aluminum element in the chromium salt to the indium salt, iron salt, zinc salt and aluminum salt is 1:0.1-1:0.1-1:0.1-1:0.1-1.

[0010] In certain embodiments, the molar ratio of the chromium element, indium element, iron element, zinc element and aluminum element in the chromium salt to the indium salt, iron salt, zinc salt and aluminum salt is 1:0.1-1:0.1-1:0.1-1:0.1-1.

[0011] In certain embodiments, the molar ratio of the chromium element, indium element, iron element, zinc element and aluminum element in the chromium salt to the indium salt, iron salt, zinc salt and aluminum salt is 1:0.25-0.5:0.25-0.5:0.25-0.5:0.25-0.5.

[0012] In certain embodiments, the molar ratio of the chromium element, indium element, iron element, zinc element and aluminum element in the chromium salt to the indium salt, iron salt, zinc salt and aluminum salt can also be 1:0.5:0.25:0.5:0.5, 1:0.25:0.25:0.5:0.5 or 1:0.5:0.25:0.5:0.25.

[0013] In certain embodiments, the chromium salt comprises at least one of chromium acetate and chromium acetylacetonate.

[0014] In certain embodiments, the indium salt includes at least one of indium acetate and indium acetylacetonate.

[0015] In certain embodiments, the iron salt comprises at least one of ferric acetate and ferric acetylacetonate.

[0016] In certain embodiments, the zinc salt comprises at least one of zinc acetate and zinc acetylacetonate.

[0017] In certain embodiments, the aluminum salt includes at least one of aluminum acetate and aluminum acetylacetonate.

[0018] The above-mentioned composite metal oxide includes chromium oxide (chemical formula: Cr2O3), indium oxide (In2O3), iron oxide (Fe2O3), zinc oxide (ZnO), and aluminum oxide (Al2O3).

[0019] In certain embodiments, the average crystal size of the composite metal oxide is 5 to 7 nm; and the composite metal oxide is crystalline.

[0020] A second aspect of the present invention provides a method for preparing a composite metal oxide, comprising the following steps:

[0021] S1: mixing indium salt, iron salt, aluminum salt, chromium salt, zinc salt and a high boiling point organic solvent, stirring and refluxing to obtain a reaction product;

[0022] S2: The reaction product is precipitated, washed, and dried to obtain the indium-doped oxide.

[0023] In certain embodiments, the molar ratio of the chromium salt to the indium salt, iron salt, zinc salt, and aluminum salt is 1:0.1-1:0.1-1:0.1-1:0.1-1.

[0024] In certain embodiments, the molar ratio of the chromium salt to the indium salt, iron salt, zinc salt, and aluminum salt is 1: 0.1-0.6: 0.1-0.6: 0.1-0.6: 0.1-0.6;

[0025] In certain embodiments, the molar ratio of the chromium salt to the indium salt, iron salt, zinc salt, and aluminum salt is 1:0.25-0.5:0.25-0.5:0.25-0.5:0.25-0.5.

[0026] In certain embodiments, the molar ratio of the chromium salt to the indium salt, iron salt, zinc salt, and aluminum salt may also be 1:0.5:0.25:0.5:0.5, 1:0.25:0.25:0.5:0.5 or 1:0.5:0.25:0.5:0.25.

[0027] In certain embodiments, the chromium salt comprises at least one of chromium acetate and chromium acetylacetonate.

[0028] In certain embodiments, the indium salt includes at least one of indium acetate and indium acetylacetonate.

[0029] In certain embodiments, the iron salt comprises at least one of ferric acetate and ferric acetylacetonate.

[0030] In certain embodiments, the zinc salt comprises at least one of zinc acetate and zinc acetylacetonate.

[0031] In certain embodiments, the aluminum salt comprises at least one of aluminum acetate and aluminum acetylacetonate.

[0032] In certain embodiments, the high boiling point organic solvent is one or more of oleic acid, oleylamine, octadecyl alcohol, and octadecene; wherein the high boiling point organic solvent acts as a solvent, a dispersant, and a surfactant.

[0033] In certain embodiments, the dosage of the high boiling point organic solvent is 1g chromium salt / 5-100mL high boiling point organic solvent; it can also be 1g chromium salt / 5-50mL high boiling point organic solvent, or 1g chromium salt / 10-30mL high boiling point organic solvent; it can also be 1g chromium salt / 20-50mL high boiling point organic solvent, or 1g chromium salt / 10mL high boiling point organic solvent, or 1g chromium salt / 15mL high boiling point organic solvent, or 1g chromium salt / 20mL high boiling point organic solvent, or 1g chromium salt / 25mL high boiling point organic solvent, or 1g chromium salt / 30mL high boiling point organic solvent.

[0034] In certain embodiments, the stirring temperature is 70-90°C; it can also be 70-80°C, 80-90°C, 75-85°C, or 70°C, 75°C, 80°C, 85°C, or 90°C.

[0035] In certain embodiments, the stirring time is 20 to 40 min; it can also be 20 to 30 min, 30 to 40 min, 25 to 35 min, or 20 min, 25 min, 30 min, 35 min, or 40 min.

[0036] In some embodiments, the temperature of the heat reflux is 150-400°C; it can also be 150-200°C, 200-250°C, 250-300°C, 300-350°C, 350-400°C, 200-300°C, or 200-350°C; it can also be 150°C, 200°C, 250°C, 300°C, 350°C, or 400°C.

[0037] In certain embodiments, the heat reflux time is 1 to 3 hours; it can also be 1.5 to 2.5 hours, it can also be 1 to 2 hours, it can also be 2 to 3 hours; it can also be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours.

[0038] In certain embodiments, the step of precipitating and washing the reaction product specifically includes: adding a detergent to the reaction product, mixing evenly, and then standing to produce a precipitate, and then using the detergent to centrifuge and / or wash the precipitate once or multiple times and then collect the precipitate; wherein the detergent is used for reactant precipitation and washing. The amount of detergent used is determined according to the specific experimental conditions and the properties of the precipitate, and is not particularly limited. The standing time is 5 to 60 minutes; it can also be 5 to 30 minutes, and can also be 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 40 minutes, 50 minutes, and 60 minutes.

[0039] In certain embodiments, the detergent comprises one or more of ethanol, ethylene glycol, methanol, and acetone.

[0040] In certain embodiments, the rotation speed of each centrifugation is 6000-10000 r / min; it can also be 7000-9000 r / min, or 6000 r / min, 7000 r / min, 8000 r / min, 9000 r / min, or 10000 r / min.

[0041] In certain embodiments, the time for each centrifugation is 4 to 15 min; it can also be 4 to 10 min, or it can be 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, or 15 min.

[0042] In certain embodiments, the drying temperature is 60-80°C; it can also be 65-75°C, it can also be 60-70°C, it can also be 70-80°C; it can also be 60°C, 65°C, 70°C, 75°C, 80°C.

[0043] In certain embodiments, the drying time is 6 to 16 hours; it can also be 6 to 12 hours, it can also be 12 to 16 hours, it can also be 8 to 14 hours, it can also be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours.

[0044] The present invention also provides a bifunctional catalyst for preparing aromatic hydrocarbons, comprising the composite metal oxide as described above.

[0045] In certain embodiments, the bifunctional catalyst further comprises a silica-alumina molecular sieve.

[0046] In certain embodiments, the silica-alumina molecular sieves are all hydrogen-type silica-alumina molecular sieves.

[0047] In certain embodiments, the silicon-aluminum ratio of the silica-aluminum molecular sieve is 20-500; it can also be 20-100; it can also be 100-200, it can also be 200-300, it can also be 300-400, it can also be 400-500; it can also be 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450 or 500.

[0048] In certain embodiments, the molecular sieve is HZSM-5 molecular sieve.

[0049] In certain embodiments, the mass ratio of the composite metal oxide to the silicon-aluminum molecular sieve is 0.25-3:1, or 0.5-3:1; 0.5-2:1, 2-3:1, 3-4:1, 4-5:1, or 0.5-1.5:1; 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 2:1, 2.5:1 or 3:1.

[0050] The present invention also provides a method for preparing the bifunctional catalyst as described above, comprising mixing the composite metal oxide as described above with a silicon-aluminum molecular sieve to obtain the bifunctional catalyst.

[0051] In certain embodiments, the mixing further includes the steps of tableting, granulation and / or sieving; preferably, the step of sieving through a 40-60 mesh sieve; it can also be a 45-55 mesh sieve, or a 40, 45, 50, 55 or 60 mesh sieve.

[0052] The present invention also provides the use of the composite metal oxide or the bifunctional catalyst as described above in the preparation of aromatic hydrocarbons using synthesis gas as a raw material.

[0053] In certain embodiments, the synthesis gas is a synthesis gas containing carbon monoxide and hydrogen or contains carbon monoxide, carbon dioxide, and hydrogen.

[0054] The present invention also provides a method for preparing aromatic hydrocarbons, the method comprising: contacting and reacting synthesis gas with the bifunctional catalyst as described above to obtain aromatic hydrocarbons.

[0055] In certain embodiments, the bifunctional catalyst needs to be pretreated before contacting with the syngas.

[0056] In certain embodiments, the pretreatment is specifically a heat treatment under a H2 atmosphere; H2 pretreatment will produce active sites - oxygen vacancies, but argon pretreatment can also be used (to remove moisture and organic matter adsorbed on the catalyst, etc.), because the reducing components in the raw gas (such as H2, CO, etc.) can also be used to reduce part of the oxides to generate oxygen vacancies.

[0057] In some embodiments, the heat treatment temperature is 300-400°C, or 300-350°C, or 350-400°C, or 320-380°C, or 340-360°C; it can also be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C.

[0058] In certain embodiments, the heat treatment time is 1 to 4 hours, or 1 to 2 hours, or 2 to 3 hours, or 3 to 4 hours, or 1 to 3 hours, or 2 to 4 hours, or 1 hour, 2 hours, 3 hours or 4 hours.

[0059] In certain embodiments, the syngas is a syngas containing carbon monoxide and hydrogen or a syngas containing carbon monoxide, carbon dioxide, and hydrogen.

[0060] In certain embodiments, the syngas includes carbon monoxide and hydrogen.

[0061] In certain embodiments, the molar ratio of carbon monoxide to hydrogen is 0.5-5:1, or 0.5-2:1, or 2-3:1, or 3-4:1, or 4-5:1, or 0.5-1.5:1; or 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, or 5:1.

[0062] In certain embodiments, the mass space velocity of the reaction is 300 to 2000 mL g cat -1 h -1 , and can also be 300-500 mL g cat -1 h -1 , and can also be 500~1000mL g cat -1 h -1 , and can also be 1000~1500mL g cat -1 h -1 , and can also be 1500~2000mL g cat -1 h -1 , and can also be 300~1000mL g cat -1 h -1 , and can also be 300, 400, 500, 500, 600, 800, 900, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700 or 1800 mL g cat -1 h -1 .

[0063] In certain embodiments, the reaction pressure is 1 to 5 MPa; it can also be 1 to 2 MPa; it can also be 2 to 3 MPa; it can also be 3 to 4 MPa; it can also be 4 to 5 MPa; it can also be 1 to 3 MPa; it can also be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5 MPa.

[0064] In certain embodiments, the reaction temperature is 300-400°C; it can also be 320-380°C, or it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C.

[0065] Beneficial effects:

[0066] The present invention provides a preparation method of an indium-doped high-entropy nanocomposite metal oxide and its application in preparing aromatic hydrocarbons from synthesis gas. The indium oxide in the composite metal oxide of the present invention has high CO hydrogenation and reverse water gas shift (RWGS) reaction activity, which can not only improve the activity of converting CO on the oxide into oxygen-containing intermediates, but also optimize the product distribution, effectively reduce the CO2 selectivity in the product, and have high aromatic hydrocarbon selectivity.

[0067] In addition, due to the easy migration characteristics of the indium element, the active metal components in the catalyst prepared by conventional methods in the field (such as co-precipitation, reverse co-precipitation, impregnation and sol-gel methods, flame spray pyrolysis, atomized spray pyrolysis and solid phase sintering) are easy to migrate, and the prepared oxide particles are relatively large, which is not conducive to the catalytic activity. The present invention uses a high-boiling point organic solvent to decompose a metal precursor at high temperature to quickly and easily prepare an indium-doped high-entropy nano-oxide. The indium-doped high-entropy nano-oxide can be used as a catalyst to form a bifunctional catalyst with a molecular sieve to catalyze the conversion of synthesis gas into aromatics. The indium-doped high-entropy catalyst has a stable structure and effectively inhibits the migration of metals to the molecular sieve, greatly improving the stability of the synthesis gas to aromatics reaction of the bifunctional catalyst; it overcomes the defects of the prior art catalyst in catalyzing the conversion of synthesis gas to aromatics, that is, the high selectivity of the byproduct CO2 and the easy migration of the active metal components. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 This is the XRD diffraction pattern of the composite oxide powder in Example 1.

[0069] Figure 2 This is the SEM image of the composite oxide powder in Example 1. DETAILED DESCRIPTION

[0070] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0071] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.

[0072] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.

[0073] The sources of the raw materials in the following examples are as follows:

[0074] Analytical grade indium acetate, ferric acetylacetonate, aluminum acetylacetonate, chromium acetylacetonate and zinc acetylacetonate were purchased from Sinopharm Chemical Reagent Co., Ltd. ZSM-5 molecular sieve (SiO2 / Al2O3=50) was purchased from Shanghai Fuyu New Materials Co., Ltd.

[0075] The room temperature described in the present invention is the conventional understanding of room temperature in the art, generally referring to 10-30°C.

[0076] Example 1

[0077] 0.29g (1mmol) indium acetate, 0.18g (0.5mmol) ferric acetylacetonate, 0.32g (1mmol) aluminum acetylacetonate, 0.71g (2mmol) chromium acetylacetonate, 0.26g (1mmol) zinc acetylacetonate were mixed and dissolved in 50mL oleylamine, heated to 80°C and heated and stirred for 30min. After the powder was completely dissolved, the reaction system was heated to 250°C and refluxed and stirred for 2h. After the reaction was completed, the temperature was cooled to room temperature, 50mL ethanol was added to produce precipitation, and the precipitate was collected by centrifugation (8000r / min, 5min), and washed with ethanol several times and then dried in an oven at 100°C for 12h to obtain indium doped high entropy nano oxide powder (the average grain size was about 5nm).

[0078] The indium-doped high entropy nano-oxide and hydrogen-type ZSM-5 molecular sieve powder are physically ground and mixed in a mass ratio of 1:1, and then pressed into tablets and granulated, and then crushed and sieved to obtain a 40-60 mesh bifunctional catalyst.

[0079] Example 2

[0080] 0.15g (0.5mmol) of indium acetate, 0.18g (0.5mmol) of ferric acetylacetonate, 0.32g (1mmol) of aluminum acetylacetonate, 0.71g (2mmol) of chromium acetylacetonate, and 0.26g (1mmol) of zinc acetylacetonate were mixed and dissolved in 50mL of oleylamine, heated to 80°C and heated and stirred for 30min. After the powder was completely dissolved, the reaction system was heated to 250°C and refluxed and stirred for 2h. After the reaction was completed, the temperature was cooled to room temperature, 50mL of ethanol was added and mixed evenly, and then precipitated after standing for 10min. The precipitate was collected by centrifugation (8000r / min, 5min), and washed with ethanol several times, and then dried in an oven at 100°C for 12h to obtain indium doped high entropy nanocomposite oxide powder (with an average grain size of about 5nm).

[0081] The indium-doped high-entropy nano-oxide and hydrogen-type ZSM-5 molecular sieve powder are physically ground and mixed in a mass ratio of 1:1, and then pressed into tablets and granulated. After crushing and sieving, a bifunctional catalyst with a mesh size of 40 to 60 is obtained.

[0082] Example 3

[0083] 0.29g (1mmol) indium acetate, 0.18g (0.5mmol) ferric acetylacetonate, 0.16g (0.5mmol) aluminum acetylacetonate, 0.71g (2mmol) chromium acetylacetonate, and 0.26g (1mmol) zinc acetylacetonate were mixed and dissolved in 50mL oleylamine, heated to 80°C and heated and stirred for 30min. After the powder was completely dissolved, the reaction system was heated to 250°C and refluxed and stirred for 2h. After the reaction was completed, the temperature was cooled to room temperature, 50mL ethanol was added and mixed evenly, and then precipitated after standing for 10min. The precipitate was collected by centrifugation (8000r / min, 5min), and washed with ethanol several times, and then dried in an oven at 100°C for 12h to obtain indium doped high entropy nanocomposite oxide powder (with an average grain size of about 5nm).

[0084] The indium-doped high entropy nano-oxide and hydrogen-type ZSM-5 molecular sieve powder are physically ground and mixed in a mass ratio of 1:1, and then pressed into tablets and granulated, and sieved to 40-60 meshes to obtain a bifunctional catalyst.

[0085] Comparative Example 1

[0086] 0.18g (0.5mmol) of ferric acetylacetonate, 0.32g (1mmol) of aluminum acetylacetonate, 0.71g (2mmol) of chromium acetylacetonate, and 0.26g (1mmol) of zinc acetylacetonate were mixed and dissolved in 50mL of oleylamine, heated to 80°C and heated and stirred for 30min. After the powder was completely dissolved, the reaction system was heated to 250°C and refluxed and stirred for 2h. After the reaction was completed, the temperature was cooled to room temperature, 50mL of ethanol was added, mixed evenly, and then allowed to stand for 10min to produce a precipitate. The precipitate was collected by centrifugation (8000r / min, 5min), and washed with ethanol several times, and then dried in an oven at 100°C overnight to obtain an indium-free doped nanocomposite oxide powder (with an average grain size of about 5nm).

[0087] The non-indium-doped nano-oxide and hydrogen-type ZSM-5 molecular sieve powder are physically ground and mixed in a mass ratio of 1:1, and then pressed into tablets and granulated. After crushing and sieving, a bifunctional catalyst with a mesh size of 40 to 60 is obtained.

[0088] Comparative Example 2

[0089] 0.29g (1mmol) indium acetate, 0.32g (1mmol) aluminum acetylacetonate, 0.71g (2mmol) chromium acetylacetonate, and 0.26g (1mmol) zinc acetylacetonate were mixed and dissolved in 50mL oleylamine, heated to 80°C and heated and stirred for 30min. After the powder was completely dissolved, the reaction system was heated to 250°C and refluxed and stirred for 2h. After the reaction was completed, the temperature was cooled to room temperature, 50mL ethanol was added and mixed evenly, and then allowed to stand for 10min to produce precipitation. The precipitate was collected by centrifugation (8000r / min, 5min), and washed with ethanol several times, and then dried in an oven at 100°C for 12h to obtain an iron-free indium doped nanocomposite oxide powder (with an average grain size of about 5nm).

[0090] The indium-doped nano-oxide and hydrogen-type ZSM-5 molecular sieve powder are physically ground and mixed in a mass ratio of 1:1, and then pressed into tablets and granulated, and then crushed and sieved to obtain a 40-60 mesh bifunctional catalyst.

[0091] Comparative Example 3

[0092] 0.29g (1mmol) indium acetate, 0.18g (0.5mmol) ferric acetylacetonate, 0.71g (2mmol) chromium acetylacetonate, and 0.26g (1mmol) zinc acetylacetonate were mixed and dissolved in 50mL oleylamine, heated to 80°C and heated and stirred for 30min. After the powder was completely dissolved, the reaction system was heated to 250°C and refluxed and stirred for 2h. After the reaction was completed, the temperature was cooled to room temperature, 50mL ethanol was added and mixed evenly, and then allowed to stand for 10min to produce precipitation. The precipitate was collected by centrifugation (8000r / min, 5min), and washed with ethanol several times, and then dried in an oven at 100°C for 12h to obtain aluminum-free indium doped nano oxide powder (with an average grain size of about 5nm).

[0093] The indium-doped nano-oxide and hydrogen-type ZSM-5 molecular sieve powder are physically ground and mixed in a mass ratio of 1:1, and then pressed into tablets and granulated, and then crushed and sieved to obtain a 40-60 mesh bifunctional catalyst.

[0094] Effect Example 1

[0095] 1. Performing X-ray diffraction (XRD) analysis on the composite oxide in Example 1 to detect whether the composite oxide is crystalline, the specific steps are as follows:

[0096] The crystallization and crystal phase properties of the oxide samples were studied using a Rigatku Ultima IV X-ray diffractometer. The tube voltage was set to 40 kV, and the tube current was set to 40 mA. "Cu Kα X-ray" was selected as the ray source of the X-ray diffractometer. The crystallization and crystal phase properties of the oxide samples were studied using a Rigatku Ultima IV X-ray diffractometer. The tube voltage was set to 40 kV, and the tube current was set to 40 mA. "Cu Kα X-ray" was selected as the ray source of the X-ray diffractometer. The 2θ range of 5–90° and the scanning step size of 2° were used to collect the oxide crystal phase data.

[0097] Results Figure 1 It can be seen that the XRD spectrum of the composite oxide has diffraction peaks with different diffraction intensities, which is crystalline rather than amorphous.

[0098] 2. The composite oxide powder obtained in Example 1 was characterized by transmission electron microscopy (TEM) (the instrument model was Tecnai G2 S-Twin, the working voltage was 200 kV), and the results were as follows: Figure 2 shown.

[0099] The X-ray diffraction (XRD) analysis in the previous article shows that Figure 1), using Jade software (software for analyzing XRD spectra), the average grain size was calculated using the Scherrer formula:

[0100] Scherrer formula: D = Kλ / (βcosθ), K is a constant;

[0101] D is the average thickness of the grain perpendicular to the crystal plane, λ is the X-ray wavelength, β is the half-height width of the diffraction peak, and θ is the diffraction angle. In the above formula, the value of the constant K is related to the definition of β. When β is the half-width height, K is 0.89; when β is the integral width, K is 1.0.

[0102] The average size of the composite oxide calculated based on the Scherrer formula is about 5 nm, specifically 5 to 7 nm.

[0103] Effect Example 2

[0104] The bifunctional catalysts obtained in Examples 1-3 and Comparative Examples 1-3 were tested, and the testing method was as follows:

[0105] 1 g of catalyst (40-60 mesh) was loaded into a fixed bed reactor. Before the feed gas was introduced, the catalyst was pretreated at 350°C in a H2 atmosphere for 1-4 h. The feed gas was synthesis gas (a mixture of CO, H2 and N2, wherein N2 was an internal standard, and the corresponding volume contents of CO, H2 and N2 were 48%, 48% and 4%, respectively). The reaction temperature was 350°C, the reaction pressure was 2 MPa, and the mass space velocity (under standard volume) was 600 mL / g. cat / h.

[0106] The reaction tail gas flows through the pipeline insulation and is transported to the gas chromatograph in gas state for online analysis. The chromatograph is equipped with a thermal conductivity detector and a packed chromatographic column as well as a hydrogen flame ionization detector (FID) and a capillary column. The former is used to detect H2, N2, CO and CO2, and the latter is used to detect the composition of hydrocarbon products. The CO conversion rate is calculated with N2 as the internal standard, and the hydrocarbon product distribution is calculated according to the carbon mole number; the results are shown in Table 1;

[0107] Table 1

[0108]

[0109]

[0110] Note, in Table 1:

[0111] 1) Reaction temperature refers to the reaction temperature when the catalyst catalyzes the raw gas during the application of the catalyst.

[0112] 2) CO conversion (CO conv.%) refers to the ratio of the volume of CO reacted to the total volume of CO introduced.

[0113] 3) The data of CO2 selectivity (CO2 Sel.%) are calculated based on all reaction products.

[0114] CO2 Sel.%=CO2 outlet / (CO inlet -CO outlet )*100%, of which CO2 outlet is the volume of CO2 in the reaction tail gas, CO inlet and CO outlet are the volume of CO reacted and the volume of CO introduced, respectively.

[0115] 4) Selectivity of hydrocarbon products (excluding CO2) (C n H m Sel. = 100% - CO2 sel.).

[0116] 5) The selectivity of CH4 (CH4 Sel.%) is CH4 Sel.% = CH4 outlet / C n H m * 100 calculated, of which CH4 outlet is the carbon molar number of CH4 in the reaction tail gas; C n H m Refers to the total amount of all hydrocarbons in the reactants, including methane, aromatics and other hydrocarbons.

[0117] 6) The selectivity of aromatics (aromatics Sel.%) is based on the hydrocarbon products obtained, and is expressed by aromatics Sel.% = aromatics outlet / C n H m Calculated, aromatics outlet is the total carbon molar number of aromatic products in the reaction tail gas; C n H m Refers to the total amount of all hydrocarbons in the reactants, including methane, aromatics and other hydrocarbons.

[0118] 7) The selectivity of other products (Other Sel.%) refers to the selectivity of products of other hydrocarbons (including C2-C5 hydrocarbons or non-aromatic hydrocarbons greater than C5) except methane and aromatics; Other Sel.% = Other outlet / C n H m Calculated, other outlet is the total carbon molar number of other products in the reaction tail gas; C n H mRefers to the total amount of all hydrocarbons in the reactants, including methane, aromatics and other hydrocarbons.

[0119] The selectivity data for aromatics and other products are calculated based on the obtained hydrocarbon products and do not include oxygen-containing gas products such as CO2.

[0120] 8) Deactivation rate (% / d): The average CO conversion rate decrease within the initial 5 days of the reaction.

[0121] In summary, compared with Comparative Examples 1-3, the bifunctional catalysts of Examples 1-3 are more effective under the same reaction conditions (350°C, 2MPa and 600mL / g cat / h), when the reaction efficiency is high, the byproduct CO2 selectivity is lower than 30%, and the catalyst deactivation rate of Examples 1-3 is significantly reduced, and the stability is higher.

[0122] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical ideas disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A composite metal oxide, characterized in that The raw materials of the composite metal oxide include chromium salt, indium salt, iron salt, zinc salt and aluminum salt.

2. The composite metal oxide according to claim 1, characterized in that The molar ratio of chromium, indium, iron, zinc and aluminum in the chromium salt, indium salt, iron salt, zinc salt and aluminum salt is 1:0.1-1:0.1-1:0.1-1: 0.1-1。 3. The composite metal oxide according to claim 1, characterized in that The chromium salt comprises at least one of chromium acetate and chromium acetylacetonate; and / or, The indium salt comprises at least one of indium acetate and indium acetylacetonate; and / or, The iron salt comprises at least one of ferric acetate and ferric acetylacetonate; and / or, The zinc salt comprises at least one of zinc acetate and zinc acetylacetonate; and / or, The aluminum salt includes at least one of aluminum acetate and aluminum acetylacetonate; and / or, The molar ratio of the chromium salt, indium salt, iron salt, zinc salt and aluminum salt is 1:0.1-1:0.1-1:0.1-1:0.1-1.

4. The composite metal oxide according to any one of claims 1 to 3, characterized in that The average grain size of the composite metal oxide is 5 to 7 nm; and / or the composite metal oxide is crystalline.

5. The method for preparing the composite metal oxide according to any one of claims 1 to 4, characterized in that: The preparation method of the composite metal oxide comprises the following steps: S1: mixing indium salt, iron salt, aluminum salt, chromium salt, zinc salt and a high boiling point organic solvent, stirring and refluxing to obtain a reaction product; S2: precipitating, washing and drying the reaction product to obtain the composite metal oxide; Preferably, the high boiling point organic solvent is one or more of oleic acid, oleylamine, octadecyl alcohol, and octadecene; Preferably, the amount of the high boiling point organic solvent is 1g chromium salt / 5-100mL high boiling point organic solvent; Preferably, the stirring temperature is 70-90°C; and / or the stirring time is 20-40 minutes; Preferably, the temperature of the heat reflux is 150-400° C.; and / or, the time of the heat reflux is 1-3 hours; Preferably, the specific steps of precipitating and washing the reaction product include: adding a detergent to the reaction product to produce a precipitate, and then centrifuging and / or washing the precipitate with the detergent and collecting the precipitate; Preferably, the detergent comprises one or more of ethanol, ethylene glycol, methanol, and acetone; Preferably, the centrifugation and / or washing comprises one or more centrifugation and / or washing; Preferably, the rotation speed of each centrifugation is 6000-10000 r / min; and / or the centrifugation time is 4-15 min.

6. A catalyst for preparing aromatic hydrocarbons, characterized in that: The catalyst comprises the composite metal oxide according to any one of claims 1 to 4 and a silicon-aluminum molecular sieve; Preferably, the mass ratio of the composite metal oxide to the silicon-aluminum molecular sieve is 0.25 to 3:

1.

7. The catalyst according to claim 6, characterized in that The silicon-aluminum ratio of the silicon-aluminum molecular sieve is 20 to 500; Preferably, the silicon-aluminum molecular sieve is a hydrogen-type silicon-aluminum molecular sieve; Preferably, the molecular sieve is HZSM-5.

8. The method for preparing the catalyst according to claim 6 or 7, characterized in that: The preparation method of the catalyst comprises mixing the composite metal oxide according to any one of claims 1 to 4 with a silicon-aluminum molecular sieve to obtain the catalyst for preparing aromatics from synthesis gas; preferably, the step of passing through a 40-60 mesh sieve is further included after the mixing.

9. Use of the composite metal oxide according to any one of claims 1 to 4 or the catalyst according to any one of claims 6 to 7 in the preparation of aromatic hydrocarbons using synthesis gas as a raw material; Preferably, the synthesis gas is a synthesis gas containing carbon monoxide and hydrogen or a synthesis gas containing carbon monoxide, carbon dioxide and hydrogen; Preferably, the synthesis gas comprises carbon monoxide and hydrogen; Preferably, the molar ratio of carbon monoxide to hydrogen is 0.5 to 5:

1.

10. A method for preparing aromatic hydrocarbons, characterized in that: The method for preparing aromatic hydrocarbons comprises: contacting and reacting synthesis gas with a catalyst to obtain aromatic hydrocarbons; Preferably, the catalyst needs to be heat treated under H2 or argon atmosphere before contacting with the synthesis gas; Preferably, the heat treatment temperature is 300-400°C; and / or the heat treatment time is 1-4h; Preferably, the mass space velocity of the reaction is 300 to 2000 mL / g cat / h; Preferably, the reaction pressure is 1 to 5 MPa; Preferably, the reaction temperature is 300-400°C.

Citation Information

Patent Citations

  • Complex-phase metal catalyst for preparing aromatic hydrocarbon from synthesis gas and preparation method of complex-phase metal catalyst

    CN113289677A

  • Catalyst for preparing aromatic hydrocarbon through conversion of synthesis gas, preparation method and application thereof

    CN114588902A

  • A short b-axis HZSM-5 zeolite molecular sieve and its preparation method and application

    CN115490243B

  • Catalyst for preparing aromatic hydrocarbon from synthesis gas as well as preparation method and application of catalyst

    CN117772181A

  • Bifunctional catalyst for preparing aromatic hydrocarbon from synthesis gas as well as preparation method and application of bifunctional catalyst

    CN117920331A